Are Women the “Keepers of the Culture”? A Study on the Gender-Specific Transmission and Development of Mainstream and Ethnic Identities using Latent Growth Curve Models - Randy Stache (Journal of International Migration and Integration, 2023)
Migration scholars repeatedly claim that mothers in migrant families are responsible for cultural preservation and that this responsibility is passed on to their daughters. In turn, male family members are claimed to be more oriented towards the majority society. This often assumed "keepers of the culture" hypothesis is assessed here using bivariate conditional latent growth curve models to track identity developments in a multigroup comparison. The analysis uses information from second-generation youth and their parents from the CILS4EU data. After a review of the mechanisms that may lead to such a gendered effect, the empirical comparison of parent-child dyads reveals that, contrary to expectations, sons and daughters undergo the same identity development during adolescence. Moreover, both parents pass on their identities to both genders in the same way. I discuss the consequences of these results on an empirical and theoretical level at the end of this paper.
Keywords: 300; Ethnic identity; Identity; Intergenerational transmission; Gender; Second generation; Latent growth curve models